DAMPAK PEMBANGUNAN PARIWISATA DALAM PENGEMBANGAN PARIWISATA PROVINSI BALI - I Nengah Wijaya; I Nyoman Kanca (Soshum: Jurnal Sosial dan Humaniora, 2013)
Indonesia has the heritage cultures and a very wide nature which can be developed as one of the incomes in the tourism sector. Now the tourism sector in Indonesia is giving the biggest income after the production of non gas and petrol. One of them is Bali that becomes the central of tourist distination in the middle of Indonesia, which attracts a lot of foreign tourists. Besides Bali, Indonesia olso has many potensial tourist destination, because those objects haven’t been well managed and lacked of attention from the government and stake-holders so the tourist are not interested to visit them. It needs a good coordination between the local society and the stake holders, in this case the government, how to manage and to organize the potential objects and culture of certain area to be developed as the tourist destination that can be visited by the tourist who are really interested to visit a new objects which is very interesting and has the superiority among others. The nature and culture which are developed on the potential tourist destination are used to be the capital in developing and promoting the regional tourist objects in general, especially in the province of Bali, such as; Besakih Temple, Tanah Lot Temple; Kuta Beach; and Candi Dasa Beach.